Pengembangan Alat Peraga Edukatif untuk Guru KB-TK Persatuan Istri Guru Malang - Indra Dharma Wijaya; Elok Nur Hamdana; Pramana Yoga Saputra; M. Afif Hendrawan; Dodit Suprianto (ISAS (Indonesian Society of Applied Science), 2026)
This activity is carried out in order to welcome the increasing development of learning media that can be applied in daily teaching. In addition, teachers are also required to be able to make changes to the learning media in their own classes to see how to improve student learning outcomes by using varied learning media. The activities in this mentoring are that teachers from the KB TK PIG will be given training and mentoring in socialization activities to increase their knowledge/understanding of how to make educational teaching aids (APE). So that it can increase the teacher's imagination in developing all aspects and intelligence in their students. The final result of this activity is expected to be that each teacher will have educational and creative learning media that have good learning value.